Development of Eco-Friendly Soy Meal Adhesives Enhanced by Ethylene Glycol Diglycidyl Ether - Xingfang Yao; Hongli Liu; Congcong Li (Advances in Polymer Technology)
The ethylene glycol diglycidyl ether (EGDE) as a viscosity reducer, plasticizing agent, and crosslinking agent was introduced into the adhesive system to improve the properties of the soy-based adhesive. The adhesive properties including viscosity, solid content, and shear adhesion of soy protein adhesive were measured. The morphology, infrared spectra, and crystallinity of the cured adhesives were evaluated with scanning electron microscopy (SEM), Fourier transform infrared (FTIR), and X-ray diffraction (XRD). The results showed that the viscosity of soybean flour (SF) adhesive was reduced by 48% and the solid content increased from 25.9% to 31.7% with the addition of 10 wt% EGDE. The wet shear strength of the plywood bonded by EGDE-modified SF adhesive was significantly improved owing to the formation of crosslinking structure in the adhesive system. The SEM, FTIR, and XRD results demonstrated that the crosslinking reaction among epoxy group of EGDE, the amino group of SF, and the hydroxyl groups of polyvinyl alcohol occurred successfully during the curing process.